Traumatic injury of the ulnar artery and ulnar nerve: clinical case report - Tavata Lizbeth, Daza Villa; Jose Luis, Villareal Salgado; Victor Hugo, Grano Gonzalez; Victor Gibran, Reyes Garcia; Jose de Jesús, Vargas Montes; Gustavo Emmanuel, Garcia Marin; Sergio E., Vazquez Lara; Mayra Yilzett, Reyes Gutierrez; Ana Laura, Ramirez Soto; Antonio, Magallón Gómez (International Surgery Journal, 2023)
Traumatic injuries to upper extremities cause vascular and nerve injuries, which is why they constitute a cause for attention in the emergency service of medical units. These injuries can cause sequelae that can affect people’s quality of life and their daily activities if they are not managed appropriately, so it is necessary to have knowledge of the anatomy to provide individualized therapeutic management. Therefore, we present the case of a female patient who suffers a traumatic injury to the forearm, which causes ulnar arterial and nerve injury. Exposing the management provided in our institution and its results.